Utilization of Learning Animation Technology in Assisting the Creation of Interactive Teaching Materials for Teachers at SMAS Kristen Soleman - Nurhajar Anugraha; Rivanky Valensius Bara; Omita Abigail; Nur Azizah Muchtar; Nurlinda Aprialliani; Angelin Marici B; Andryanto Aman; Muhammad Qadri; Dyah Utari Yusa Wardhani (Jurnal Abdimas Cendekiawan Indonesia, 2024)
The teacher's job is to increase student interest in learning with the aim of improving student achievement in the learning process. One of the problems faced by teachers at SMAS Kristen Soleman is the lack of knowledge and skills in the use of animation learning technology, so that the teaching materials produced are less attractive and become one of the factors in decreasing student interest in the learning process. The purpose of this community service is to improve knowledge and skills through training and mentoring in making interactive teaching materials using animated learning technologies such as Canva, Kahoot, and Powtoon to teachers at SMAS Kristen Soleman. The implementation method is carried out starting from the preparation stage (field observation, literature study, and partner identification), the implementation stage (training and mentoring), to the evaluation stage using pre-test and post-test before and after training and mentoring is carried out. Based on the evaluation results of training and mentoring teachers in making interactive teaching materials using animated learning technology, it shows an increase in knowledge from 41.7% to 100%, where teachers already knew interactive teaching materials using animation learning technology. Meanwhile, teachers' skills increased from 12.5% to 91.7%.